2016
DOI: 10.4062/biomolther.2016.091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuroactive Constituents of the Ethyl Acetate Fraction from Cyperi Rhizoma Using Bioactivity-Guided Fractionation

Abstract: Cyperi Rhizoma (CR), the rhizome of Cyperus rotundus L., exhibits neuroprotective effects in in vitro and in vivo models of neuronal diseases. Nevertheless, no study has aimed at finding the neuroactive constituent(s) of CR. In this study, we identified active compounds in a CR extract (CRE) using bioactivity-guided fractionation. We first compared the anti-oxidative and neuroprotective activities of four fractions and the CRE total extract. Only the ethyl acetate (EA) fraction revealed strong activity, and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[66] This compound is reported to exhibit mild antioxidant effect based on DPPH antiradical assay with IC 50 value >500 μM. [67] Compound (13)…”
Section: Uhplc-qtof-ms/ms Based Metabolite Profile Of C Reflexamentioning
confidence: 99%
“…[66] This compound is reported to exhibit mild antioxidant effect based on DPPH antiradical assay with IC 50 value >500 μM. [67] Compound (13)…”
Section: Uhplc-qtof-ms/ms Based Metabolite Profile Of C Reflexamentioning
confidence: 99%
“…However, to the best of our knowledge, there is no evidence supporting the effect of active constituents of CRE in gynecologic disorders including endometriosis. In a previous study, we found that α-cyperone is the most abundant and active component of CRE [ 44 , 45 , 46 , 47 ]. In these regards, we have examined the anti-endometriotic effect of α-cyperone in human endometriotic 12Z cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chuanxiong Rhizoma is known to improve blood circulation, removing blood stasis, promoting qi and relieving pain [2]. Cyperi Rhizoma can regulate qi, relieve depression, regulate menstruation and relieve pain [3]. The use of Chuanxiong Rhizoma-Cyperi Rhizoma combination is first stated in Danxi Xinfa (a comprehensive medical book written by Zhu Zhenheng in 1481) for the alleviation of headache with a syndrome of phlegm syncope and migraine headache [4].…”
Section: Introductionmentioning
confidence: 99%